Perceived Burden and Healthy Lifestyle Behavior in Family Caregivers of the Persons with Disabilities in Bukhara - Hülya YÜCEL; Nurhayat KORKMAZ (Bezmiâlem Science)
Objective: Family caregiving is a common tradition to Uzbekistan. The responsibilities of caring for a person with disabilities may cause caregivers to develop risky health behaviors and become a burden for them. The aim of this study was to determine the relationship between perceived caregiver burden and healthy lifestyle behavior in family members caring for young persons living with disabilities under the age of 24 years. Methods: The sociodemographic characteristics of the participants were recorded. The number of children in the family, duration of care period, disability group of the one who is cared, duration and type of disability, age and gender of the young person were asked. The Zarit Burden Interview and the Health Promoting Lifestyle Profile II (HPLP II) were used. Results: Out of 155 caregivers, 89.8% were women and 10.2% were men. There was no correlation between burden and HPLP II in general (r=0.048, p=0.551). A positive correlation was found between burden and nutrition, one of the sub-dimensions of the HPLP II (r=0.038; p=0.016), whereas negative correlations were found between burden and health responsibility and stress management sub-dimensions (r=-0.170, p=0.034; r=-0.184, p=0.022). Conclusion: Perceived burden did not affect healthy lifestyle behavior in general. This may be due to the positive meaning that Uzbeks attach to caregiving. This study is the first in Uzbekistan concerning the effect of caregiving to young persons with disabilities on family members. The results show that family caregivers might require additional support for stress management and health responsibility.